The Rise of Intersectionality in Sociological Discourse: A Global Bibliometric and Thematic Analysis (2014–2024) - Rukminiarti; Kurniawati, Juliana; Safitra, Linda; Susiyanto; Pakpahan, Fransiskus Novrianto (Socio-political Communication and Policy Review, 2024)
Intersectionality has emerged as a pivotal framework in sociology for examining how overlapping social identities, such as race, gender, and class, contribute to systemic inequalities. Despite its growing influence, there remains a lack of systematic analysis of its global scholarly impact, particularly outside Western academia. This study addresses this gap by employing bibliometric and thematic methods to map the development of intersectionality in sociological research from 2014 to 2024. Using a mixed-methods approach, we analyzed 580 Scopus-indexed documents through co-citation and bibliographic coupling in VOSviewer, identifying key intellectual clusters and geographic trends. The findings reveal a strong dominance of North American and European scholarship, with limited contributions from the Global South, highlighting disparities in knowledge production. Four major research clusters emerged, focusing on public health, methodological challenges, social reproduction, and health equity, while emerging themes include digital inequalities, climate justice, and epistemic decolonization. These results underscore the need for more inclusive methodologies that incorporate non-Western perspectives and practical applications in policy and activism. The study concludes by advocating for future research to expand intersectional analyses into critical areas such as climate justice, digital health equity, and the decolonization of knowledge, ensuring the framework remains relevant in addressing contemporary social inequalities.